Linguistic Deviation and Techniques of Translation in Spring of Kumari Tears - Ambhita Dhyaningrum (Universitas Sanata Dharma, 2020)
A linguistic deviation occurs when a writer chooses not to abide the rules of a standard language. It is one of the ways to achieve artistic merit. Through linguistic deviation, a writer can communicate unique experiences that cannot be effectively communicated by means of normal communicative resources. It is also a linguistic phenomenon that has an important psychological effect on readers. This article aimed at analyzing the linguistic deviation in Mata Air Air Mata Kumari and the techniques of translation in its English version, Spring of Kumari Tears. The three most used types of linguistic deviation found are semantic deviation (55.77 %), graphological deviation (20.19 %), and grammatical deviation (11.54 %). The rest are phonological and lexical deviation in a small percentage. Meanwhile, the three most used translation techniques are reduction (28.85 %), linguistic compression (23.07 %), and discursive creation (10.58 %). The rest are modulation, amplification, transposition, established equivalent, borrowing, and deletion. The findings indicated that the author mostly used semantic, graphological, and grammatical deviation to create unexpected surprises and make a strong impression to the readers as the means to attain the artistic merit. However, the artistic merit is simplified by the use of the translation techniques which compress the linguistic elements, reduce the message of the original text, and create temporary equivalence that is out of context. As a result, the translated version tends to be more concise and succinct.